Neural mechanisms of antidepressant efficacy of the dopamine receptor agonist pramipexole in treatment of bipolar depression - Mah, Linda (2010)
The D(2)/D(3) receptor agonist pramipexole has clinical efficacy as an antidepressant, but its neural mechanisms are unknown. We used (18)FDG-PET to investigate the cerebral metabolic effects of pramipexole augmentation of mood stabilizers in bipolar II depression. Fifteen bipolar II depressed patients on mood stabilizers were imaged at baseline and following 6 wk of pramipexole (n=7) or placebo (n=8) augmentation. Relative to placebo, pramipexole treatment was associated with reductions in normalized metabolism in bilateral orbitofrontal cortex, left ventrolateral prefrontal cortex (PFC), and right anteromedial PFC. Voxel-wise analyses additionally showed decreased normalized metabolism in the left inferior parietal cortex and medial frontopolar cortical (BA 10P) area of the anteromedial PFC following pramipexole treatment. These pramipexole-induced effects on regional metabolism suggest a mechanism of antidepressant action distinct from that previously reported under serotonin reuptake inhibitor treatment and appear compatible with evidence that the central dopaminergic system plays a role in the pathophysiology of bipolar depression.